[Cost-Utility Analysis of Dupilumab for the Treatment of Severe Atopic Dermatitis in Children and Adolescents in Italy] - Galli, Elena; Pedone, Maria Paola; Dobreva, Miryana; Bitonti, Rossella; Di Turi, Roberta (Farmeconomia. Health Economics and Therapeutic Pathways, 2022)
BACKGROUND AND OBJECTIVE: Atopic dermatitis (AD) is a chronic, multifactorial, inflammatory condition characterized by a significant impact on patients’ quality of life. Dupilumab is reimbursed by the Italian Medicines Agency (AIFA) for the treatment of adolescent and adult patients with severe AD (according to AIFA registry criteria). Recently, dupilumab has been reimbursed in the treatment of children with severe AD. The objective of this analysis was to estimate the incremental cost-utility ratio (ICUR) of dupilumab compared to current supportive care (SC), for the treatment of severe AD in children (6-11 years) and adolescents (12-17 years) in Italy.MATERIALS AND METHODS: Cost-effectiveness analysis was conducted using a 1-year decision tree followed by a Markov model over a lifetime period. The base case analysis was performed on the overall population of the LIBERTY AD ADOL (NCT03054428) and LIBERTY AD PEDS (NCT03345914) studies, adopting the National Health Service (NHS) perspective. The following costs were considered: acquisition of treatment, management of disease, adverse events and complications. The robustness of the model was tested through sensitivity analysis. In addition, a scenario analysis adopting the social perspective was performed.RESULTS: In the base case, over a lifetime, dupilumab was more effective than SC in both children and adolescents (+2.44 and +1.62 quality-adjusted life years—QALYs, respectively). The introduction of dupilumab generated an increase in treatment costs (+€ 64,800 and +€ 52,853 € for children and adolescents, respectively), partially offset by a decrease in the costs of disease management and complications. Incremental cost-utility ratios (ICURs) were € 21,189 per QALY gained, for children, and € 26,569 per QALY gained, for adolescents. In both cases, the ICUR was lower than the willingness to pay threshold considered in Italy (€ 50,000 per QALY gained). Both the deterministic and probabilistic sensitivity analysis confirmed the robustness of the base case results. Finally, the scenario analysis, adopting the social perspective, showed coherent results compared to the base case.DISCUSSION: Dupilumab is a cost-effective option for the treatment of children and adolescents with severe AD eligible for systemic treatment in Italy compared to SC, from both the NHS and social perspective, confirming the results obtained in the adult population.